PENGEMBANGAN USAHA BUDIDAYA IKAN JELAWAT Business Development of Jelawat Fish Cultivation - Muhammad Adnan Zain (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
Research was aims to determine Knowing the factors that support development and that inhibit the development of fish farming jelawat andvdevelopment of fish cultivation jelawat. To determine the development of farming jelawat used SWOT analysis in addition to determining the direction of development of fish culture jelawat. Research was conducted in kecamatan karang intan kabupaten Banjar which is the location of fish farming jelawat. From the research results can be known fairly promising prospects for business development both interms of price and consumer demand, but needs to be improved in terms ofcultivation management. Development of fish farming is expected to increase theincome of fish farmers and also keep the fish is a commodity jelawat kalimantan localfish can be maintained sustainability.